PERUBAHAN PERILAKU TOKOH UTAMA DALAM CERITA PENDEK UMARAH KARYA KAMIL KAILANI (BEHAVIORISME PERSPEKTIF BURRHUS FREDERIC SKINNER): PERUBAHAN PERILAKU DALAM CERPEN “UMARAH” KARYA KAMIL KAILANI: ANALISIS PERSPEKTIF SKINNER - Izzat Imaniya; Ilma Nailu Fitriani (Program Studi Bahasa dan Sastra Arab STIABI Riyadul 'Ulum, 2026)
This study discusses the behavioral changes experienced by the main character in the short story Umarah by Kamil Kailani. Umarah is portrayed as a lazy and annoying child who often makes his mother angry. His negative behavior gradually changes after receiving stimuli from his environment, including his mother, workplace, and the Sultan of the kingdom. The stimuli received by Umarah produce responses that contribute to the process of behavioral change within himself. Through various experiences, Umarah and his mother eventually enjoy a better life with the Sultan in the kingdom. This study aims to describe the stimuli, responses, and effects experienced by the main character in the short story Umarah based on the behaviorism theory of Burrhus Frederic Skinner. This research employs a descriptive qualitative method using reading and note-taking techniques for data collection. The results show that the main character receives twelve stimuli from his environment, and these stimuli generate responses that shape the process of behavioral change within Umarah. This study implies that the environment plays an important role in shaping individual behavior. Future studies are recommended to examine psychological aspects or moral values in other works by Kamil Kailani.